Influence of Extrudate-Based Textural Properties on Pellet Molding Quality - Wenxiu Tian; Xue Li; Wenjie Li; Aile Xue; Minyue Zheng; Xiao Lin; Yanlong Hong (MDPI AG, 2023)
As the precursor of pellets, the extrudate has a direct impact on the molding quality of the pellets. Therefore, the correlation between the surface roughness of the extrudates and the molding quality of pellets with pure microcrystalline cellulose (MCC) formulations and those containing traditional Chinese medicine (TCM) formulations was explored. MCC was used as a pelleting agent, mixer torque rheometry (MTR) was used to guide the optimal dosage of the wetting agent, and TCM extracts (drug loadings of 20% to 40%) were selected as model drugs to prepare the extrudates and pellets under the same extrusion spheronization process conditions. The surface roughness and texture parameters of extrudates were analyzed via a microscope and texture analyzer, respectively, and the quality of pellets was evaluated. The extrudate roughness of the pure MCC prescription decreased and then increased with increasing water addition, while the extrudate roughness of the prescription containing TCM extracts tended to increase and then decrease. The addition of water affected the extrudate properties, with TCM extract molecules filling gaps in the MCC structure, leading to rough surfaces. The extrudate roughness of the TCM prescriptions was significantly greater than that of the pure MCC prescriptions at optimal water addition levels, resulting in ideal pellets.